The importance of financial management and entrepeneurship competencies for school principals - Nadia Fairuza Azzahra; Latasha Safira (Center for Indonesian Policy Studies (CIPS), 2022)
Both school financial management and entrepreneurship are acknowledged as important competencies to acquire for school principals in Indonesia. Appropriate school financial management is important to ensure school funds are spent efficiently and effectively to support the provision of quality education services. Entrepreneurship, on the other hand, incorporates values such as leadership, self-sufficiency, and resourcefulness that are necessary to develop their schools, supervise their teachers and education personnel, as well as and effectively address future challenges. The unprecedented COVID-19 pandemic has highlighted the importance of these two competencies in the face of adversity. For example, while schools have been given an increase in flexibility to utilize the School Operational Assistance according to their school's individual needs, this also implies that the freedom comes with responsibility to manage their funds appropriately. In addition, schools, especially those catering to low-income families, also faced financial challenges due to the low-enrollment. This demonstrates the need to implement entrepreneurship practices to respond to these challenges.
Keywords: 330; Betriebliche Finanzwirtschaft; Entrepreneurship; Schule; Qualifikation; Betriebliches Bildungsmanagement; Weiterbildung; Führungskräfte; Lehrkräfte; Indonesien